Self-Esteem and Satisfaction with Holland's SDS - Byrne, Thomas P. (Canadian Journal of Counselling and Psychotherapy, 2012)
Two studies were conducted to assess the influence of self-esteem on student satisfaction with Holland's Self-Directed Search (SDS). Eleventh grade students from two high schools in Kings County, Nova Scotia rated the SDS according to two criteria: reasonableness and usefulness of the results. Two Likert type items were used to quantify the criteria. To differentiate high and low self-esteem groups, a median split of the total P scores of the Tennessee Self-Concept Scale was used. The satisfaction ratings of the high and low self-esteem groups were compared by means of T tests. In each study the high esteem group reported significantly greater satisfaction (p < .05) on the second criterion, planned use of the SDS results.